2017
DOI: 10.3747/co.24.3238
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Value of Low Estrogen Receptor Expression in Breast Cancer

Abstract: Purpose Anti-hormonal therapy (tamoxifen) is recommended for estrogen receptor (er)-positive breast cancer (bca); however, its effect on low-receptor cancers is unclear. We retrospectively evaluated the effect of adjuvant tamoxifen in patients with weakly er-positive bca. MethodsWe identified 2221 bca patients who had been er-tested by ligand-based assay (lba) during [1976][1977][1978][1979][1980][1981][1982][1983][1984][1985][1986][1987][1988][1989][1990][1991][1992][1993][1994][1995] and who had been treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 26 publications
0
17
0
5
Order By: Relevance
“…чувствительными (гормонопозитивными) считались опухоли, в которых при иммуногистохимическом исследовании выявлена ядерная экспрессия рецепторов эстрогенов и (или) прогестерона (ER/PR) ≥ 1 %; и в данном случае пациенткам рекомендовалась эндокринотерапия, в том числе и по поводу мРМЖ [4][5][6]. Однако исследования последних лет поставили под сомнение такой подход; было показано, что течение и прогноз заболевания у пациенток с положительной, но низкой экспрессией ER (ER-low -1-10 % позитивно окрашенных ядер) более неблагоприятный и выигрыш от назначения эндокринотерапии не такой значимый, как у больных с экспрессией ER > 10 % [7,8]. Так, по данным крупного метаанализа с включением 21 457 больных показано, что 5-летняя эндокринотерапия тамоксифеном значимо снижает риск рецидива (в первые 5 лет -на 47 %, в последующие 5 лет -на 32 %; р < 0,00001) и риск смерти (в первые 5 лет на 29 %, в последующие 5 лет -на 33 %; p < 0,0001) для ER+ РМЖ, но не для больных c экспрессией ER-low [8].…”
Section: The Analysis Of the Current Strategy For The Treatment Of Adunclassified
See 1 more Smart Citation
“…чувствительными (гормонопозитивными) считались опухоли, в которых при иммуногистохимическом исследовании выявлена ядерная экспрессия рецепторов эстрогенов и (или) прогестерона (ER/PR) ≥ 1 %; и в данном случае пациенткам рекомендовалась эндокринотерапия, в том числе и по поводу мРМЖ [4][5][6]. Однако исследования последних лет поставили под сомнение такой подход; было показано, что течение и прогноз заболевания у пациенток с положительной, но низкой экспрессией ER (ER-low -1-10 % позитивно окрашенных ядер) более неблагоприятный и выигрыш от назначения эндокринотерапии не такой значимый, как у больных с экспрессией ER > 10 % [7,8]. Так, по данным крупного метаанализа с включением 21 457 больных показано, что 5-летняя эндокринотерапия тамоксифеном значимо снижает риск рецидива (в первые 5 лет -на 47 %, в последующие 5 лет -на 32 %; р < 0,00001) и риск смерти (в первые 5 лет на 29 %, в последующие 5 лет -на 33 %; p < 0,0001) для ER+ РМЖ, но не для больных c экспрессией ER-low [8].…”
Section: The Analysis Of the Current Strategy For The Treatment Of Adunclassified
“…Более того, больные с низкой экспрессией ER-low имеют хороший ответ на неоадъювантную химиотерапию (высокую частоту полных морфологических ответов), а при наличии резидуальной опухоли -такой же неблагоприятный прогноз, как и больные с тройным негативным раком [7][8][9][10]. Возможным объяснением данного феномена могут быть результаты исследования B. S. Sheffield и соавт., согласно которым опухоли с низкой экспрессией ER (3-5 баллов по шкале Allred, по данным ИГХ-анализа) при генетическом анализе PAM50 только в 10 % случаев являются истинными люминальными раками, а в 90 % случаев имеют генетический профиль базально-подобного или HER2-enrichподтипов [10].…”
Section: The Analysis Of the Current Strategy For The Treatment Of Adunclassified
“…However, breast cancers with low hormone receptor expression are usually still considered as hormone receptor positive (= luminal) subtype [6]. Various studies showed that therapy response and outcome of patients with tumors showing low hormone receptor expression between 1 and 10% (LowHR) are more similar to triple negative breast cancer (TNBC), the so-called basal subtype [6][7][8][9][10][11][12][13]. These results are supported by molecular studies, using RNA-based classification algorithms [14].…”
Section: Introductionmentioning
confidence: 96%
“…As such, using 1% as a cutoff for ER positivity has been challenged and an alternate cutoff for positivity set at 10% positivity has been commonly suggested [13]. In several comprehensive studies, tumors with a low level of ER-staining (1-10%) share more clinical and pathologic characteristics with ERnegative than to ER-positive tumors, which show little benefit from endocrine therapy [13][14][15][16]. Therefore, further evaluation on the characteristics, patient prognoses, and treatment efficacy in low-ER-staining tumors is warranted.…”
Section: Introductionmentioning
confidence: 99%